Effect of sonic versus manual supervised toothbrushing on both clinical and biochemical profiles of patients with desquamative gingivitis associated with oral lichen planus: A randomized controlled trial. Issue 2 (25th December 2018) - Bianco, Laura; Romano, Federica; Maggiora, Marina; Bongiovanni, Loretta; Guzzi, Nicoletta; Curmei, Elena; Arduino, Paolo Giacomo; Aimetti, Mario
Abstract: Objectives: The aim of this randomized, parallel‐design, clinical trial was to investigate the effectiveness of an intensive plaque control programme with sonic versus manual toothbrushing on clinical outcomes and gingival crevicular fluid (GCF) levels of matrix metalloproteinases (MMP) in desquamative gingivitis (DG) patients. Methods: A total of 32 patients affected by DG secondary to oral lichen planus (OLP) were consecutively recruited and randomly assigned to a test (n = 16) and control (n = 16) group. Both groups were enrolled in an intensive control programme comprising supragingival scaling and polishing, and brush‐specific instructions for a period of 8 weeks. The treatment of interest (test) was the use of a sonic‐powered toothbrush, and the standard treatment (control) was the utilization of a soft‐bristle manual toothbrush for twice‐daily home oral hygiene procedures. Periodontal parameters, patient‐centred outcomes, MMP‐1 and MMP‐9 GCF levels were evaluated at baseline and 8 weeks after starting the programme. Results: The plaque control programme resulted in statistically significant reduction in periodontal parameters with consequent improvement in the clinical features, painful symptoms and severity of DG lesions in both groups (all P  < 0.001). When a sonic toothbrush was used, there was a more significant decrease in clinical indices, mucosal disease scores and GCF levels of MMP‐1 and MMP‐9. Conclusions: This clinical trial reported the effectiveness of a combined protocol based on professional oral hygiene and supervised toothbrushing in OLP patients with DG. The daily use of a sonic toothbrush would seem to perform better in the short term.